Light‐Driven Intramolecular C−N Cross‐Coupling via a Long‐Lived Photoactive Photoisomer Complex. (29th August 2019) - Jing, Dong; Lu, Cong; Chen, Zhuo; Jin, Songyang; Xie, Lijuan; Meng, Ziyi; Su, Zhishan; Zheng, Ke
Abstract: Reported herein is a visible‐light‐driven intramolecular C−N cross‐coupling reaction under mild reaction conditions (metal‐ and photocatalyst‐free, at room temperature) via a long‐lived photoactive photoisomer complex. This strategy was used to rapidly prepare the N ‐substituted polycyclic quinazolinone derivatives with a broad substrate scope (>50 examples) and further exploited to synthesize the natural products tryptanthrin, rutaecarpine, and their analogues. The success of gram‐scale synthesis and solar‐driven transformation, as well as promising tumor‐suppressing biological activity, proves the potential of this strategy for practical applications. Mechanistic investigations, including control experiments, DFT calculations, UV‐vis spectroscopy, EPR, and X‐ray single‐crystal structure of the key intermediate, provides insight into the mechanism. Abstract : Milde Gabe : Eine durch sichtbares Licht angetriebene intramolekulare C‐N‐Kreuzkupplung wird vorgestellt, die unter milden Bedingungen (metall‐ und photokatalysatorfrei, Raumtemperatur) über einen langlebigen photoaktiven Photoisomerkomplex verläuft. Mit ihr wurden N‐substituierte polycyclische Chinazolinonderivate mit großem Substratumfang sowie Naturstoffe synthetisiert. Einige Produkte zeigen vielversprechende tumorsuppressive biologische Aktivität.